IMPLEMENTASI AKAD ISTISHNA DALAM PEMBIAYAAN RUMAH TANPA BANK DEVELOPER PROPERTI SYARIAH : Studi Kasus pada PT. Amanah Barokah Santosa di Bekasi - Kiswanto; Irvan Iswandi; Ahmad Asrof Fitri (Melati Institute, 2023)
The title of this research is the implementation of istishna akad in house finance without bank applied by shariah property developer PT Amanah Barokah Santosa. This research studied the implementation of istishna akad in house finance without bank. Istishna akad is order commerce and it is one form of commerce frequently implemented by the community in the process of owning a house. The problem of this research was how is the implementation of istishna akad in house finance without bank that occurs at sharia property developer PT Amanah Barokah Santosa in Bekasi. The type of this research was descriptive qualitative with elaboration related to the existed problem solving. The results of this research show that PT. Amanah Barokah Santosa has implemented istishna akad well and free of riba/interest. It also embraced the concept of not implementing riba or interest, there is no penalty, it does not guarantee the goods that do not belong to the buyer, the price determined prevails until the house is completely paid, the guarantee applied is in the form of goods (rahn), and it is true that it uses house finance system without bank.